Colestimide Lowers Plasma Glucose Levels and Increases Plasma Glucagon-like Peptide-1 (7-36) Levels in Patients with Type 2 Diabetes Mellitus Complicated by Hypercholesterolemia - Tatsuya Suzuki; Kenzo Oba; Yoshimasa Igari; Noriaki Matsumura; Kentaro Watanabe; Shoko Futami‐Suda; Hiroko Yasuoka; Motoshi Ouchi; Kazunari Suzuki; Yoshiaki Kigawa; Hiroshi Nakano (2007)
Background: Colestimide has been reported to lower blood glucose levels in patients with type 2 diabetes complicated by hypercholesterolemia. Aim: To examine the mechanism by which colestimide decreases plasma glucose levels in the above patients. Methods: A total of 16 inpatients with type 2 diabetes complicated by hypercholesterolemia received colestimide for 1 week after their plasma glucose levels stabilized. We measured plasma glucose, serum immunoreactive insulin (IRI), serum lipid, plasma glucagon, and plasma glucagon-like peptide-1 (GLP-1) levels. These variables at baseline and 1 week of colestimide administration were compared. Results: Preprandial plasma glucose levels (baseline: 132 ± 33 mg/dL vs. completion: 118 ± 43 mg/dL, P=0.073) tended to decrease after colestimide administration, while 1-hr postprandial plasma glucose levels (baseline: 208 ± 49 mg/dL vs. completion: 166 ± 30 mg/dL, P<0.001) and 2-hr postprandial plasma glucose levels (baseline: 209 ± 56 mg/dL vs. completion: 178 ± 39 mg/dL, P=0.015) decreased significantly at 1 week of colestimide administration. The 2-hr postprandial plasma GLP-1 level was significantly (P=0.015) higher at 1 week of colestimide administration as compared with the baseline level, while there were no significant changes in preprandial and 1-hr postprandial plasma GLP-1 levels. Conclusions: The GLP-1-increasing activity of colestimide may explain, at least in part, the mechanism of its blood glucose-lowering activity in patients with type 2 diabetes complicated by hypercholesterolemia.